Literature and Politics in the Tanzimat Period: Relations between İbrahim Şinasi and Sultan Abdülmecid - Ebuzer Karaaslan (İstanbul Üniversitesi Edebiyat Fakültesi Türk Dili ve Edebiyatı Dergisi)
The Tanzimat is considered the milestone of modern Turkish literature and the beginning of literature breaking free from the auspices and dominance of politics. When questioning who the intellectual and literary “master” of this period is, there seems to be a broad consensus around İbrahim Şinasi. Şinasi, seen as the pioneer of the political literature of the Tanzimat period, is regarded by some Turkish literary historians as the first Turkish literary figure to break the tradition of literature being tied to the palace and the Sublime Porte. This study focuses on the nature of Şinasi’s relationship with Sultan Abdülmecid, aiming to question the truth of the role attributed to him and enhance our understanding of the structure of the relationship between literature and politics in that period. The research method was document analysis in this study. In this context, archival documents, primary sources, research and reviews were utilized. This study revealed that Şinasi composed panegyrics, devised chronograms, authored and composed a march, and wrote a theater play influenced by these connections. The findings obtained in this study suggest that a significant discrepancy between the role historians assign to Şinasi and the nature of his relationship with the Sultan.